Expression Regulation Mechanisms of Sea Urchin (Strongylocentrotus intermedius) Under the High Temperature: New Evidence for the miRNA-mRNA Interaction Involvement - Han, Lingshu; Quan, Zijiao; Wu, Yanglei; Hao, Pengfei; Wang, Wenpei; Li, Yuanxin; Zhang, Xianglei; Liu, Peng; Gao, Chuang; Wang, Heng; Wang, Luo; Zhang, Weijie; et al. (Frontiers in Genetics, 2022)
In the context of global warming and continuous high temperatures in the northern part of China during summer, the mortality rate of our main breeding species, Strongylocentrotus intermedius, reached 80% in 2020. How sea urchins respond to high temperatures is of great concern to academia and industry. In this study, we examined the antioxidant enzyme activities of different color tube-footed sea urchins under heat stress and compared their transcriptome and microRNA (miRNA) profiles using RNA-Seq. The results showed that the antioxidant enzyme activities of sea urchins were altered by thermal stress, and the changes in peroxidase activities of red tube-footed sea urchins were particularly significant. Investigations revealed that 1,079 differentially expressed genes (DEGs), 11 DE miRNAs, and 104 “DE miRNA-DEG” pairs in total were detected in sea urchins under high temperature stress. Several mRNA and miRNAs were significantly changed (e.g. HSP70, DnaJ11, HYAL, CALR, miR-184-p5, miR-92a, miR-92c, and miR-124-p5), suggesting these genes and miRNAs exerted important functions in response to high temperature. At the transcriptional level, red tube-footed sea urchins were found to be more sensitive to high temperature and could respond to high temperature rapidly. DE miRNA-mRNA network showed that miR-92b-3p and PC-5p-7420 were the most corresponding miRNAs. Five mRNAs (DnaJ11, SAR1B, CALR, HYOU1, TUBA) may be potential markers of sea urchin response to high temperature. Possible interaction between miRNA-mRNA could be linked to protein folding in the endoplasmic reticulum, Phagosomes, and calcium transport. This study provides a theoretical basis for the molecular mechanism of sea urchin heat tolerance and information that will aid in the selection and breeding of sea urchins with high temperature tolerance.